2013
DOI: 10.1155/2013/909860
|View full text |Cite
|
Sign up to set email alerts
|

Off-Label Use of Ondansetron in Pregnancy in Western Australia

Abstract: Aims. Nausea and vomiting of pregnancy is the most common medical condition in pregnancy. There is an increasing trend to prescribe ondansetron although its safety for use in pregnancy has not been established. Methods. Exposed pregnancies were all births in Western Australia, 2002–2005, where the mother was dispensed ondansetron under the Australian Pharmaceutical Benefits Scheme, compared with all other births during the same period. Outcomes investigated include maternal and child characteristics, birth def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 29 publications
2
60
1
1
Order By: Relevance
“…An Australian study reported that serotonin antagonists were more likely prescribed to non‐smoking women in agreement with our results . The same study also found they were used more for women in higher socioeconomic groups and Caucasian women, in contrast to our study . To the best of our knowledge, no study to date has assessed whether hospital prescribing for HG is compliant with national or local guidelines in England.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…An Australian study reported that serotonin antagonists were more likely prescribed to non‐smoking women in agreement with our results . The same study also found they were used more for women in higher socioeconomic groups and Caucasian women, in contrast to our study . To the best of our knowledge, no study to date has assessed whether hospital prescribing for HG is compliant with national or local guidelines in England.…”
Section: Discussionsupporting
confidence: 90%
“…23 The same study also found they were used more for women in higher socioeconomic groups and Caucasian women, in contrast to our study. 32 To the best of our knowledge, no study to date has assessed whether hospital prescribing for HG is compliant with national or local guidelines in England.…”
Section: Comparisons With Previous Studiesmentioning
confidence: 99%
“…1 The post-market setting provides the only opportunity to understand the benefits and risks of drug use in these populations. Compared to the elderly (represented primarily by DVA clients), we know little about medicines use in children [35][36][37][38] and pregnant women [39][40][41][42][43][44] and found no studies examining the outcomes of medicines use in Australian children. The studies of drug use and outcomes in pregnant women highlight Australia's capacity for pharmacoepidemiological research using linked routinely collected data in populations other than the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of drug use and outcomes in pregnant women highlight Australia's capacity for pharmacoepidemiological research using linked routinely collected data in populations other than the elderly. [39][40][41][42][43][44][45] Australia is in a powerful position to conduct wholeof-population pharmacoepidemiological research due to its universal drug coverage for 23 million citizens and the more than 200 million prescriptions generated each year. 8 The significant investment in data linkage infrastructure through the Population Health Research Network has supported Australian states and territories to build a network enabling health data collected around the nation for health-related research purposes; 28 the recent establishment of Data Integrating Authorities will support the integration of Commonwealth data with state-based collections.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, an UL and OL use of licensed medicines is not illegal and the outcomes should not be underestimated particularly when all other options of licensed medicines are unavailable, exhausted, not tolerated, ineffective or unsuitable for patient's healthcare needs. For these underlying reasons, in some instances an UL and OL medicine application may be the only choice or the best available access to therapy for vulnerable population such as obstetric (Colvin et al, 2013) pediatric ('tJong et al, 2001;Bavdekar and Gogtay, 2005;Bellis, et al, 2013;Silva et al, 2014), oncologic (Pool and Dooley, 2004;Soares, 2005), geriatric (Dautzenberg et al, 2009) and psychiatric (Chouinard, 2006;Hall et al, 2001) patients as well as patient on palliative care or with terminal disease condition (Pavis and Wilcock, 2001;Culshaw et al, 2013;). Indeed, OL prescribing is also common for so-called therapeutic orphan populations and/or rare diseases treatments and special condition (Hampton, 2007;Conroy et al 2000;Shah et al, 2007).…”
Section: Statistical Data About Ol Use Of Licensed Medicines and Ul Mmentioning
confidence: 99%